1982
DOI: 10.1007/bf01809309
|View full text |Cite
|
Sign up to set email alerts
|

Intracranial meningioma with subdural membrane

Abstract: A case of meningioma with subdural membrane formation, but without a collection of subdural haematoma, is presented. The histological picture of the membrane was similar to that found in a chronic subdural haematoma. Relevant literature is reviewed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

1992
1992
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…The assoeiation of a men ingeal tumor with a subdural ha emat oma (2. 16) and that of a meningioma with a subdural neomembrane without bloody collection (22) have been report ed too. It is tempting to speculate a possible influe nce of ste roid hormones on both th e lesions .…”
Section: Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…The assoeiation of a men ingeal tumor with a subdural ha emat oma (2. 16) and that of a meningioma with a subdural neomembrane without bloody collection (22) have been report ed too. It is tempting to speculate a possible influe nce of ste roid hormones on both th e lesions .…”
Section: Patientsmentioning
confidence: 99%
“…formation of a meningioma (2) or of a sarcoma (16) inside the HEM of CSOH patient s, as weil as the ass ociation of a meningioma with a newly-formed subdural membrane without a collection ofblood (22).…”
Section: It Is Interesting To Remin D Also the Reportedmentioning
confidence: 99%
“…We found 115 reported bleeding meningiomas of the CNS, including our two patients 18 –96 . The age and gender were recorded in 102 patients (Table 1).…”
Section: Discussionmentioning
confidence: 81%
“… 15 20 Patil observed that a dural reaction of the meningioma formed the neomembrane similar to the outer membrane of CSDH despite neither subdural fluid collection nor blood clots. 21 Moreover, they noticed that tumor cells were not expressed in the neomembrane originating from the meningioma. 21 In our case, the outer membrane of the subdural hematoma was entirely infiltrated by meningioma cells.…”
Section: Discussionmentioning
confidence: 99%
“… 21 Moreover, they noticed that tumor cells were not expressed in the neomembrane originating from the meningioma. 21 In our case, the outer membrane of the subdural hematoma was entirely infiltrated by meningioma cells. To the best of our knowledge, no previous report has mentioned similar findings to our case.…”
Section: Discussionmentioning
confidence: 99%